Second trimester maternal serum markers and a predictive model for predicting fetal hemoglobin Bart's disease - Tongprasert F. (2014)
Objective: To compare the levels of maternal serum α-fetoprotein (AFP), unconjugated estriol (uE3) and free β-human chorionic gonadotropin (free β-hCG) between pregnancies with fetal Hb Bart's disease and unaffected pregnancies. Methods: 148 pregnancies at risk of fetal Hb Bart's disease scheduled for cordocentesis at 18 to 22 weeks were prospectively recruited into the study. AFP, uE3 and free β-hCG concentrations were measured before cordocentesis and the final fetal diagnosis of Hb Bart's disease was based on fetal Hb typing using high-performance liquid chromatography. Results: AFP and free β-hCG were significantly higher whereas uE3 was lower in women with fetal Hb Bart's disease than those with unaffected fetuses (1.94 MoM, 1.38 MoM and 0.81 MoM respectively). Hb Bart's predictive model; probability = 1/1+e-[2.876 + 1.333(AFP) - 6.310(uE3)], effectively predicted fetal Hb Bart's disease (AUC ROC 0.91, 95% CI 0.84-0.97) with 61.5% sensitivity and 98.1% specificity using a cut-off probability at greater than 0.5. Conclusions: In triple test, serum AFP and hCG levels are significantly higher while serum uE3 is significantly lower in pregnancies with fetal Hb Bart's disease. Hb Bart's predictive model included AFP and uE3 is relatively effective and may be helpful in Hb Bart's prenatal screening. © 2013 Informa UK, Ltd.